The Cult Towards Courage in Oral Epic and Chivalri Literature - Berisha, Labinot (Acta Universitatis Danubius. Communicatio, 2022)
The cult of bravery and deeds, of the horse, of weapons, and of the beautiful woman is old. It can be said with certainty that it has been present in epic oral poetry since the beginning of its existence. Ancient epics such as "Iliad" and "Odyssey" etc. convince us of this. In literary works, which dealt with such aspects of human action, the cult of bravery and deeds took on a marked dimension. These works had a great influence not only on the development of epic genres, but also on other literary genres of different periods. Works of this character were called chivalric literature and had a wide spread. This literature was characterized by the symbiosis of the creator, poet or singer, with the public; in it the miracles of the actions of the knights, the various descriptions of heroic acts, of the actions to kidnap (rob) beautiful girls, to gain fame, and to preserve personal and family honor are expressed. Literature with such features developed especially in France and is associated with gesture songs, which made an impact on other European literatures, as the initiator is the writer, Chrétien, who began to write in the second half of the XII century. Works of this quality were spread by the so-called jugglers, who were wandering poets. Through them was revived the "old fame" of the brave actions (res gestae) of the brave and the former leaders. Even our knightly songs are deeply permeated by a spirit of chivalrous cult, namely the testimony of bravery and chivalric deeds.